2017
DOI: 10.21608/epx.2018.6648
|View full text |Cite
|
Sign up to set email alerts
|

University Students’ knowledge, attitudes, and practices towards the National Premarital Screening Program of Saudi Arabia

Abstract: Background: There is an elevated rate of hereditary hemoglobinopathies in Arab populations. To address this, the Saudi government has implemented a mandatory premarital screening (PMS) program. Nevertheless, reports have shown that 48% of genetically incompatible partners have decided to marry. To address this, more information is needed on people's beliefs on these issues. Aim: To investigate the knowledge, attitudes, and practices of Taif University students toward the national PMS program. Materials and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 0 publications
3
12
0
Order By: Relevance
“…Furthermore, they were concerned that the screening results would not support their selections. This results are in agreement with Melaibari et al (2017), which reported that the most common reason for PMSGC rejection for nearly all participants was the fear of receiving incompatible PMSGC results and consequently the termination of an otherwise favourable marriage. This is in the line with Al-Khaldi et al (2002), which stated that health science students in Abha agreed that the prevention of disease transmission to them and their offspring was the primary reason for partaking in a PMSGC rather than to certify the health of their partners.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, they were concerned that the screening results would not support their selections. This results are in agreement with Melaibari et al (2017), which reported that the most common reason for PMSGC rejection for nearly all participants was the fear of receiving incompatible PMSGC results and consequently the termination of an otherwise favourable marriage. This is in the line with Al-Khaldi et al (2002), which stated that health science students in Abha agreed that the prevention of disease transmission to them and their offspring was the primary reason for partaking in a PMSGC rather than to certify the health of their partners.…”
Section: Discussionsupporting
confidence: 92%
“…The existence of inherited or chronic infectious diseases can interrupt a marriage whether it affects the partners or their broods. Therefore, it is important to ensure the couples' capability prior to marriage by detecting those diseases and the possibility of its presentation in their offspring (Al-Enezi and Mitra, 2017;Melaibari et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Each of these studies was conducted in the United States, except for Melaibari et al's study, which investigated views of young adults in Saudi Arabia on the national premarital screening program of the country. 9 Findings were similar across the board, with studies indicating a general lack of knowledge about reproductive options and sickle cell inheritance, and confusion about adequacy of resources for this information. The qualitative studies we identified follow a similar trendexploring attitudes, beliefs, and reproductive decisionmaking of individuals with SCD or SCT.…”
Section: Introductionmentioning
confidence: 68%
“…In other studies, this percentage was higher. For example, it was 82.9% in a study at Taif University [ 39 ], 67.1% in another study in Saudi Arabia [ 33 ], and more than 60% in a population-based study in Saudi Arabia [ 40 ]. This could be due to the availability of prenatal diagnosis and pregnancy termination (under certain circumstances) in Qatar, as shown in other studies [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could reflect the level of religious awareness among this high-level-educated population and the importance of dissemination of clear religious messages supporting PMS as a preventive strategy toward a healthy population. A study at Al-Taif University showed a different association, where only 5.2% of students disagreed that PMS interferes with destiny [ 39 ]. A similar misconception about Islamic principles that led to PMS rejection was also reported in other studies [ 1 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%